AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN KOPI ARABIKA (Coffea arabica L.) PADA EDEMA TIKUS - Desy Muliana Wenas; Lisana Sidqi Aliya; Nita Usikatul Janah (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
The coffee leaf contains flavonoid compounds that are known as an antiinflammation agent. The study aimed to determine antiinflammatory activity of arabica coffee's leaf extract (Coffea arabica L.) against edema on white rat soles of carrageenan-induced rats. The research began with the maceration extraction of coffee leaf in 70% ethanol. The inflammation test was held by measuring the formation of edema using a plethysmometer. The dosages of arabica coffee leaf extract used were 60 mg.kg-1, 120 mg.kg-1, and 180 mg.kg-1 rat weight of white Sprague Dawley rat (Rattus norvegicus). The data were analyzed by Kruskal Wallis and Mann Whitney non-parametric tests. Phytochemical screening showed that arabica coffee leaf extract contained flavonoid, saponin, alkaloid, tannin and triterpenoids compound. The arabica coffee leaf extract showed the best antiinflammatory activity at the dose of 180 mg.kg-1 rat weight with 71.66% inhibition percentage at the 5th hour, which was better than the positive control (66.91% edema inhibition at the same hour). This result determined that the leaf extract of arabica coffee had antiinflammatory activity. However, it is necessary to study the acute and chronic toxicity and formulates the arabica coffee leaf extract as a pharmacy product.